Conditioning, bonding, and cementation of orthodontic appliances in teeth with enamel alterations. Literature review - Vallejo Monrroy, Catherine Andrea; Pedrosa Astudillo, Jackeline Beatriz; Ortega López, Miriam Fernanda; Puebla Ramos, Lorenzo; Noborikawa Kohatsu, Andrés Kenichi; Ramos Montiel, Ronald Roossevelt (Odontología, 2021)
Objective: Carry out a narrative review on the information available about the conditioning, bonding, and cementation of orthodontic appliances in teeth with enamel alterations. Materials and methods: Descriptive, retrospective research with a documentary design was carried out. 178 scientific articles were found in reliable sources such as Google Scholar, Scielo, PubMed, Scopus, Springer, Scientific Reports, and Elsevier related to the conditioning, bonding, and cementation of orthodontic appliances in teeth with enamel alterations; of which, 29 articles met the inclusion criteria and were selected. Results: Etching with 37% phosphoric acid plus composites remineralizing ingredients were more effective during orthodontic treatment in teeth with enamel alterations than other studied materials such as sodium hypochlorite, hydrochloric acid, bromelain gel, and papain gel. Conclusion: The materials that improve the conditioning, bonding, and cementation of orthodontic appliances in teeth with enamel alterations are phosphoric acid and sodium hypochlorite (NaOCI) with a concentration of 5.25%. Also, using deproteinizing agents could improve the resistance of the composite to eviction.